ZRANB3 is an African-specific type 2 diabetes locus associated with beta-cell mass and insulin response - Adebowale A. Adeyemo (Nature Portfolio, 2019)
Type 2 diabetes (T2D) is prevalent in populations worldwide, however, mostly studied in European and mixed-ancestry populations. Here, the authors perform a genome-wide association study for T2D in over 5,000 sub-Saharan Africans and identify a locus, ZRANB3, that is specific for this population.